Software Complex for Investigation of Remote Inter-Phase Short Circuits at Lines of 6–10 (35) kW with Supply on One Side - F. A. Romaniuk; I. L. Novash; V. Yu. Roumiantsev; N. N. Bobko; V. A. Ustimovitch (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers methodology for creation of software complex while using Fortran software modules and DELPHI object programming system. Software complex is designed for investigation of line operational modes of 6–10 (35) kW with supply on one side and remote inter-phase short circuits.